'Do as WE Do': Teaching World Englishes in a General English Course to Thai Students. (April 2023) - Rajprasit, Krich
The spread of English throughout the world has led to the language acquiring the status of an international language and has also led to the emergence of many varieties of English in different parts of the world, commonly referred to as world Englishes (WE). In this regard, WE advocates are making efforts to raise awareness of English diversity and have highlighted the need for learners and educators to develop positive attitudes toward such diversity. In order to promote greater awareness and more positive attitudes in language-learning classrooms, various WE-informed pedagogical principles for language teaching have been developed by WE practitioner-researchers. However, research building on the growing body of reports on English language teaching (ELT) classroom innovation and how to better share such innovation in practice remains scarce in some under-researched contexts, such as Thai classrooms. Consequently, the present study aims to address a gap by offering a practical example of how to incorporate WE into an English language learning course for university students in the English as a foreign language context. To further justify its significance, the study also shares the written reflections of students on their experiences with WE-oriented learning activities. These reflections revealed positive attitudes toward linguistic diversity and their improved understanding of the sociolinguistic reality of English after taking part in the innovative WE-oriented learning activities. The present study showcases innovative classroom practice that differs completely from the traditional classroom in terms of its particular focus on raising the awareness of WE, and it is also hoped that such classroom practice may provide some guidance for the further implementation of WE in other ELT contexts.